2005
DOI: 10.1385/endo:27:1:063
|View full text |Cite
|
Sign up to set email alerts
|

Thyrotoxic Hypokalemic Periodic Paralysis in a Turkish Male with Graves' Disease: A Rare Case Report and Review of the Literature

Abstract: Thyrotoxic hypokalemic periodic paralysis (THPP) is a very rare complication of thyrotoxicosis in whites, but is more frequently reported in individuals of Asian descent. Hypokalemia, with associated flaccid paralysis, and signs of hyperthyroidism, are the hallmark. We have reported a case of a 28-yr-old white man with Graves' disease presenting with a 2-wk history of episodic flaccid quadriplegia. Physical examination disclosed a resting tachycardia and symmetrical, proximal weakness involving both arms and l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…Recently, cases of THPP have been reported increasingly for Turkish Caucasian populations. To date, six such cases have been reported in the English literature since 2004 5–10 . However, there are other case reports in the Turkish literature and in congress presentations, with the first reported case being published in 1968 11–30 .…”
Section: Introductionmentioning
confidence: 99%
“…Recently, cases of THPP have been reported increasingly for Turkish Caucasian populations. To date, six such cases have been reported in the English literature since 2004 5–10 . However, there are other case reports in the Turkish literature and in congress presentations, with the first reported case being published in 1968 11–30 .…”
Section: Introductionmentioning
confidence: 99%
“…The onset of premonitory muscle aches became warning signs for some of them to get active and work "work off" an impending attack. Trans and Reeves in Australia reported a case of similar paralysis in a gender assigned man, who was on maintenance testosterone and was also receiving interferon alpha for HCV infection 23 while Tigas et al working in Greece observed this disorder in a patient following intravenous administration of methyl prednisolone 24 which are unlike the situation in this patient who was not on any medication prior to the onset of the paralyses but has Graves disease which has been variously reported to be the commonest cause 2,3,4 . The hallmark of Thyrotoxic periodic paralysis is hypokalaemia 25,26 but occasionally if the patient is at the recovery phase of the paralysis, the serum potassium can be normal 26.…”
Section: Discussionmentioning
confidence: 93%
“…Besides these latter factors, resting after exercise can also increase Na + / K + -ATPase activity in skeletal muscle, promoting an influx of potassium. 3,4 Therefore, B receptor blockage, anti-thyroid drugs and instructing patients to avoid such precipitating factors as high-carbohydrate meals are recommended for treatment and prophylaxis of THPP instead of administering potassium only. 5 Unless there are cardiopulmonary complications, KCl infusion should be given, however, at a slow rate because it may result in rebound hyperkalemia as potassium shifts back into the intravascular compartment.…”
Section: Letter To the Editormentioning
confidence: 99%